2006
DOI: 10.1002/jhet.5570430626
|View full text |Cite
|
Sign up to set email alerts
|

A simple two steps ytterbium triflate‐catalysed preparation of 2,2‐dimethyl‐2h‐chromenes from salicylaldehydes and 2‐methylpropene

Abstract: The preparation of various 2,2-dimethyl-2H-chromenes was achieved in two steps via an ytterbium triflate-catalysed reaction between salicylaldehydes, trimethylorthoformate and 2-methylpropene. From salicylaldehyde, two reaction products were characterised: 4-methoxy-2,2-dimethylchroman and 2-(1,3-dimethoxy-3-methylbutyl)phenol. The former compound probably results from a Lewis acid-catalysed [2+4] cycloaddition between the intermediate quinonemethide and 2-methylpropene whereas the latter may occur via a react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…2 Nearly all of the methods for the synthesis of chromenes involve the closure of the pyran ring on a substrate containing a pre-formed phenol unit of the type 2 . Recent representative methods include Claisen rearrangement 3 or electrophile induced cyclization of aryl propargyl ethers, 4 palladium-catalyzed 5 and selenium-mediated 2a cyclization of 2-butenylphenols, ring closing metathesis, 6 cyclization of salicylaldehydes with enamines, 7 Wittig olefination, 8 Petasis reaction of salicylaldehydes 9 and the reaction of salicylaldehydes with vinyltrifluoroborates, 10 palladium catalyzed oxidative cyclization of aryl-3-butenyl ethers, 11 ene 12 and Baylis-Hillman 13 reactions of salicylaldehydes, ylide induced annulation, 14 enolization of vinylquinones, 15 cyclization onto 3,4-epoxy alcohols, 16 the reactions of phenols with α, β-unsaturated aldehydes, 17 the oxa-Michael-aldol/Henry reaction of salicylaldehydes 18 and the dehydrative cyclizations of 2-(1-hydroxy-2-propenyl)phenols. 19 Of all the methods of the myriad, to the best of our knowledge, there is not a single one in which both rings of the chromene core are constructed at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…2 Nearly all of the methods for the synthesis of chromenes involve the closure of the pyran ring on a substrate containing a pre-formed phenol unit of the type 2 . Recent representative methods include Claisen rearrangement 3 or electrophile induced cyclization of aryl propargyl ethers, 4 palladium-catalyzed 5 and selenium-mediated 2a cyclization of 2-butenylphenols, ring closing metathesis, 6 cyclization of salicylaldehydes with enamines, 7 Wittig olefination, 8 Petasis reaction of salicylaldehydes 9 and the reaction of salicylaldehydes with vinyltrifluoroborates, 10 palladium catalyzed oxidative cyclization of aryl-3-butenyl ethers, 11 ene 12 and Baylis-Hillman 13 reactions of salicylaldehydes, ylide induced annulation, 14 enolization of vinylquinones, 15 cyclization onto 3,4-epoxy alcohols, 16 the reactions of phenols with α, β-unsaturated aldehydes, 17 the oxa-Michael-aldol/Henry reaction of salicylaldehydes 18 and the dehydrative cyclizations of 2-(1-hydroxy-2-propenyl)phenols. 19 Of all the methods of the myriad, to the best of our knowledge, there is not a single one in which both rings of the chromene core are constructed at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…4 We have reported an approach addressing this issue, the synthesis of the chromene ring system by an ytterbium triflate catalysed reaction between isobutene and various salicylaldehydes via the corresponding quinonemethides formed in situ. 6 In the course of this work, we observed that 2,5-dihydroxybenzaldehyde gave the corresponding chromene in low yield, along with unidentified side products. We also found more recently that, under the same reaction conditions, the readily available 2-bromo-3,6dihydroxybenzaldehyde (3) 7 led to the corresponding 5bromo-2,2-dimethyl-2H-chromen-6-ol (4) in 65% yield.…”
mentioning
confidence: 74%
“…A previously described procedure was followed: 6 In a 300-mL thick bottle tube fitted with a PTFE-faced screw-cap, 2-bromo-3,6dihydroxybenzaldehyde 7 (3; 4.00 g, 29.0 mmol) was dissolved in CH 2 Cl 2 (185 mL). HC(OMe) 3 (4.25 mL, 37.7 mmol) and Yb(OTf) 3 •xH 2 O (0.78 g, 1.3 mmol) were then added.…”
Section: -Bromo-22-dimethyl-2h-chromen-6-ol (4)mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, aldehydes including hydroxyl functional groups at the 3- and 5-positions could not be fully isolated because other unidentified compounds were formed with similar polarity that prevented a complete purification. 374 …”
Section: Orthoester Reactions In Organic Solventsmentioning
confidence: 99%